A distopia como aceno a uma estética do lapso em canções do Radiohead - Pedro Henrique Dutra Martins Rocha Elias (2019)
This study investigates depictions of dystopia in songs by the English group Radiohead, in attention to instants of transcendence approached in light of a lapse aesthetics. The analyses constitute a chronologically linear path in the repertoire, starting with the song “Fake Plastic Trees”, from the album The Bends (1995), followed by the subsequent albums OK Computer (1997) and Kid A (2000). These moments are connected by a conceptual thread: while “Fake Plastic Trees” contains the germ of a dystopian sentiment, compressed under the radiophonic format, OK Computer shows a broad picture of contemporary vices whose awareness between different protagonists results in disorientation and melancoly; finally, Kid A transfers the terms of this conflict to the musical interplay, creating a metaphor of reification in the impossibility of articulating the subject in the space of creation. The focus in lapses of transcendence, in spite of the limitations inherent to the culture industry, is grounded in a review of traditional philosophical categories, particularly among the writings of Theodor Adorno. In preparation of the ground where the analyses take place, Radiohead’s repertoire is placed between two core narratives: one related to musical form, the evolution from rock’n’roll to art rock; the other, dedicated to the pattern of representation, with an overview of dystopia from the origins in literature to reconfigurations in languages such as cinema and music.